Dirty Entrepreneurship : The Intersectionality of Entrepreneurs’ Dirty Recycling Businesses - Shepherd, Dean A.; Parida, Vinit; Wincent, Joakim (SAGE Publications, 2024)
Although much has been made about heroic entrepreneurs, there is recent interest in less glamorous forms of entrepreneurship. The least glamorous is dirty entrepreneurship. In this study, we used an inductive approach and a sample of entrepreneurs engaged in dirty plastic recycling businesses to develop an intersectionality model of entrepreneurs’ dirty recycling businesses. This inductive study offers new insights into how individuals’ intersectionality pushes them into dirty entrepreneurship, how they approach their businesses, and who they stigmatize. Interestingly, individuals’ dirty place and caste push them into dirty entrepreneurship that collectively cleans the environment despite not intending to do so.
Keywords: sustainable; manuscripts: specialty areas; qualitative; research methods; psychology; manuscripts: general areas; decision-making; trust; social capital; entrepreneurship; fi=Strateginen johtaminen|en=Strategic Management|